Dual Bands of Substrate Integrated Waveguide Antennas for 5G Applications - et. al., Sarah Majid Hameed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
For K-band applications, this article presents a dual band circular slot fixed on a substrate integrated waveguide (SIW) antenna. The simulation result of the antenna includes of a micro strip probe with two rounded slots put in on the top of the radiation plane and located one on top of another for increased bandwidth. This probe was intended with a “dielectric constant” of 2.2 as well as a thickness of 1.5 mm on a Roger layer. Better antenna vibrates at 23.43 GHZ and 30.16 GHZ with a fractional bandwidth of 2.9 GHZ and 1.1 GHZ, consequently. The peak gain attained is about (6.63 and 6.09 dB) above the working frequencies, united. This makes it perfect for K and Ka applications with strong corresponding and returns loss features. The analysis and construction assessment of the proposed probe was led by the EM simulator, CST Microwave Studio